Influence of selected organic micropollutants on organisms = Wpływ wybranych mikrozanieczyszczeń organicznych na organizmy - Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article describes the toxicity of organic micropollutants on tested microorganisms. Itis a current issue because organic micropollutants are identified in all elements of environmental (surface water, ground water, soils) and in food products.
Keywords: TEQ; TEF; PCDD; PCDF; PCB; IARC; toxicity; toksyczność